2004
DOI: 10.1680/geot.2004.54.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Particle breakage during shearing of a carbonate sand

Abstract: A series of ring shear tests was conducted to investigate the development of particle breakage with shear strain for a carbonate sand. It was found that at very large displacements the soil reached a stable grading, but that the final grading was dependent on both the applied normal stress and the initial grading. The particle breakage caused a volumetric compression, which again ceased only when the stable grading had been attained, emphasising that critical states as observed at much smaller strains in triax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
289
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(312 citation statements)
references
References 14 publications
16
289
3
4
Order By: Relevance
“…Both single-particle crushing and fragmentation process of an assembly of particles subjected to shearing or compaction have been subject to experimental investigations in civil engineering and particle technology [10][11][12][13][14][15][16][17][18][19][20][21][22]. The compressive strength of a single particle, its variability, and size dependence are essential for understanding the collective response of a granular material to applied loading.…”
Section: Introductionmentioning
confidence: 99%
“…Both single-particle crushing and fragmentation process of an assembly of particles subjected to shearing or compaction have been subject to experimental investigations in civil engineering and particle technology [10][11][12][13][14][15][16][17][18][19][20][21][22]. The compressive strength of a single particle, its variability, and size dependence are essential for understanding the collective response of a granular material to applied loading.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent detailed studies have considered the relationship between particle crushing and soil mechanical behaviour ( [1,[3][4][5]4,7,9,23,25,28,36]). From the point of view of constitutive modelling, the question to be addressed is how microscopic degradation phenomena, such as grain crushing, affect the macroscopic properties of a granular aggregate, ideally deducing macroscopic constitutive equations from micromechanical consideration of some underlying microscopic process [25].…”
Section: Introductionmentioning
confidence: 99%
“…It may be concluded that particle breakage continues to very large strains (7500%), far beyond those reached in the direct shear tests reported in the paper (16-25%). Coop et al (2004) concluded that at very large strains a constant grading should be reached, but that constant grading is dependent not only on the normal stress applied but also on the uniformity and absolute particle size of the initial grading (Fig. 15).…”
Section: Discussionmentioning
confidence: 99%